Dimensi-Dimensi Islam - Agus Rifki Ridwan; Agnes Meilinda; Khairunnisa Luthfiyah; Diyana Diyana; Ulpa Wulandari (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Islam is a holistic religion, covering various dimensions of life that are harmoniously integrated. The dimensions of Islam consist of aspects of faith (belief), worship (ritual), morality (morality), and muamalah (social interaction). In the dimension of faith, Islam emphasizes faith in Allah, angels, holy books, apostles, the last days, and destiny, which are the spiritual foundation of every Muslim. The dimension of worship includes the practice of Islamic teachings in the form of formal rituals such as prayer, fasting, zakat, and hajj, which not only bring individuals closer to Allah, but also strengthen social solidarity. On the moral dimension, Islam teaches universal moral values, such as honesty, patience, and justice, which form the noble character of the individual. Meanwhile, the muamalah dimension includes the procedures for social, economic, and political interaction, which is based on the principles of justice, balance, and mutual benefit. These four dimensions complement each other, creating a balanced framework of life between a vertical relationship with God and a horizontal relationship with fellow humans and the environment. This research aims to explore the meaning, function, and relevance of the Islamic dimensions in modern life. With a descriptive qualitative approach, the results of the study show that a comprehensive understanding of the dimensions of Islam can be a solution to various contemporary challenges, such as moral crises, social inequality, and environmental degradation. This study recommends the holistic application of Islamic values in daily life to create a civilized social order.